Role of alcoholic extract of Roket (Eruca sativa) leaves on male reproduction of experimentally induced-oxidative stressed rats: Baraa Najim AL-Okaily and Ahmed Jasim Nowfel - AL-Okaily, Baraa Najim (The Iraqi Journal of Veterinary Medicine, 2015)
This study conducted to find out the protective role of ethanolic extract of Eruca sativa leaves against the deleterious effect of hydrogen peroxide on some aspect of male reproduction in adult rats. Forty adult male rats were randomly assigned into four equal groups as follows: control group received tap water (untreated); group T1 were received tap water containing 0.5% H2O2; group T2 were received tap water containing 0.5% H2O2 plus administration of 300 mg/kg. B.W. ethanolic extract of Eruca sativa leaves and group T3 administration ethanolic extract of Eruca sativa leaves only at the same dose of group T2. All treatments continued for 60 days. At the end of the experiment, samples of tests and epididymis tissues were taken to prepare histological sections for measurement the diameter of seminiferous tubules, thickness of epithelial cells of seminiferous tubules and histological examination of testes and epididymis. The results in Group T1 showed a significant decrease in the diameter and thickness of epithelial cells of seminiferous tubules, but these parameters clarified a significant increase in T2 and T3 groups as compared with T1 group. Histological sections of testis and epididymis in group T1 revealed incomplete spermatogenesis, cell debris, vacculation of Sertoli cells and view sperms in the lumen of seminiferous tubules and epididymis. Besides, normal obvious histological architecture of seminiferous tubules and epididymis with complete spermatogenesis were shown in sections of testis and epididymis of T2 and T3 groups’ as compared to T1. In conclusion, hydrogen peroxide may impair spermatogenesis, furthermore, the results confirm the protective role of E. sativa leaves extract against oxidative stress induced by H2O2 in rats.